Musical Instruments Acoustics and Vibration - Tronchin, Lamberto (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The study of the acoustic and vibrational characteristics of musical instruments in terms of their mechanical behavior, sound emission, and characteristics started thousands of years ago, and among the physicists and mathematicians that addressed this matter, we should at least recognize Leonardo da Vinci, with his experimental water organ, and Ernst Chladni, who discovered nodal patterns on rigid surfaces such as soundboards. The growing awareness of our intangible cultural heritage and the need to better understand our roots in the field of music have contributed to increasing the efforts to extend our knowledge in this field, defining new physical parameters, extending the analysis to other musical instruments, and developing new methods to synthesize sound from musical instruments using a simple keyboard.